2009
DOI: 10.1158/1078-0432.ccr-08-1694
|View full text |Cite
|
Sign up to set email alerts
|

CD20-Directed Small Modular Immunopharmaceutical, TRU-015, Depletes Normal and Malignant B Cells

Abstract: Purpose: CD20-directed therapy with rituximab is effective in many patients with malignant lymphoma or follicular lymphoma. However, relapse frequently occurs within 1year, and patients become increasingly refractory to retreatment. Our purpose was to produce a compact, single-chain CD20-targeting immunotherapeutic that could offer therapeutic advantages in the treatment of B-cell lymphoma. Experimental Design: Rituximab is a chimeric antibody containing two heavy chains and two light chains. Here, we describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…TRU-015, engineered as a fusion of a single-chain Fv specific for CD20 to an Fc fragment devoid of CH1 and CL has, by design, a decreased ability to engage complement components and complement-dependent cytotoxicity but retains strong antibody-dependent cytotoxicity (ADCC) and potent direct signaling activity in vivo (Burge et al, 2008). It has been shown that it can effectively deplete B lymphocytes in a dose-dependent manner in non-human primates and improve survival in mouse xenograft tumor models (Hayden-Ledbetter et al, 2009). In an open-label dose escalation phase I trial in patients with RA, TRU-015 was associated with dose-dependent B-cell depletion and found to have an acceptable tolerability profile (Burge et al, 2008).…”
Section: Fc-fusion Proteins and Delivery Approaches In Clinical Develmentioning
confidence: 99%
“…TRU-015, engineered as a fusion of a single-chain Fv specific for CD20 to an Fc fragment devoid of CH1 and CL has, by design, a decreased ability to engage complement components and complement-dependent cytotoxicity but retains strong antibody-dependent cytotoxicity (ADCC) and potent direct signaling activity in vivo (Burge et al, 2008). It has been shown that it can effectively deplete B lymphocytes in a dose-dependent manner in non-human primates and improve survival in mouse xenograft tumor models (Hayden-Ledbetter et al, 2009). In an open-label dose escalation phase I trial in patients with RA, TRU-015 was associated with dose-dependent B-cell depletion and found to have an acceptable tolerability profile (Burge et al, 2008).…”
Section: Fc-fusion Proteins and Delivery Approaches In Clinical Develmentioning
confidence: 99%
“…TRU-015, is another third generation anti-CD20 molecule that is a small modular immunopharmaceutical drug composed of human IgG1 Fc and CH2 and CH3 hinge regions linked directly to an anti-CD20 scFv. [56][57][58] It is slightly smaller than an IgG and has high ADCC and low complement activating ability. It is currently in Phase 2 clinical development for RA.…”
Section: Perspectivementioning
confidence: 99%
“…A small modular immunopharmaceutical (SMIP) is a singlechain peptide construct, smaller than a mAb, which contains an antigen-binding (variable) domain, a hinge, and an effector domain, such as an Ig constant region, selected according to a specific therapeutic purpose [138]. Intravenous administration of an anti-CD20 SMIP, 2LM20-4, induced a more sustained B cell depletion than did rituximab in a preclinical cynomolgus monkey study [139].…”
Section: Smip Biologicsmentioning
confidence: 99%